Searching phase II enzymes inducers, from Michael acceptor-[1, 2]dithiolethione hybrids, as cancer chemopreventive agents. (June 2015) - Couto, Marcos; Ovalle, Stefani de; Cabrera, Mauricio; Cerecetto, Hugo; González, Mercedes
Background: Cancer chemoprevention involves the carcinogenic process prevention, delay or reverse by the administration of chemopreventive agents, which are able to suppress or block the carcinogen metabolic activation/formation. The increased activity of phase II detoxification enzymes such as quinone-reductase (QR) and glutation- S -transferase (GST) correlates with the protection against chemically-induced carcinogenesis. It has been shown that synthetic chalcones and 3 H -[1, 2]-dithiole-3-thiones promote expression of genes involved in chemoprevention.Materials & Methods: Herein, the induction of phase II enzymes by designed Michael acceptor-dithiolethione hybrids was studied.Results & Discussion: Hybrids5 and7 displayed the induction of quinone-reductase and glutation- S -transferase in vitro in the same order on the wild-type mouse-hepatoma Hepa 1c1c7 and on the aryl-hydrocarbon-nuclear-translocator (Arnt)-defective mutant BPrc1 cells indicating that7 displays the best chemopreventive potential.